PROSPEK PENGGUNAAN Sarcocystis singaporensis UNTUK PENGENDALIAN BIOLOGIS POPULASI TIKUS SAWAH (Rattus argentiventer) (Prospect of Sarcocystis singaporensis for the Biological Control of Rice Field Rats (Rattus argentiventer) Population) - . Muchrodji; Yanto Santosa; Abdul Haris Mustari (Department of Forest Resources Conservation and Ecotourism - IPB University, 2006)
Rice field rats are important pests of paddy crop in Indonesia, because many unsuccessful paddy crop attacked by rats. Many rodenticide types are produced, especially chemical rodenticide type the actually effect of unfavourable to environment. Biological rodenticide types (bio rodenticide) are still developed slimmest even still very rare, though bio rodenticide types are environmental friendliness. Bio rodenticide type that developed by PPPG Pertanian is using Sarcocystis singaporensis, that is a specific parasite microorganism type lives in rats body. S. singaporensis reproduces sexually in the intestine of reticulated python (Pyhton reticulatus) and transmitted via faeces (in form of sporocyst) to various rats species (Jaekel, 2001). In rats body, the parasite multiplies inside the cell of blood vessel until it forms cyst in muscle, causing rats become death. This parasite not endanger both for human being and also snake. Dosage of S. singaporensis in killing male and also female rice field rats do not related by the age class of rats. The effect on giving Sarcocystis singaporensis on day of death to female rice field rats do not related by the age class of rats, however day of death of the young male rats has quicker than adult rats.Key words : Sarcocystis singaporensis, rodenticide, biological rodenticide, Rattus argentiventer.